Analysis of Mean Time Between Failures and Reliability of a 150 kV Circuit Breaker at Bantul Substation Using the Maximum Likelihood Estimation Method - Rachmanto, Arsya Hilmana; Nugraha, Candra Febri (Universitas Muhammadiyah Surakarta, 2024)
As technology advances in the modern era, the need and consumption of electrical energy in society has increased rapidly. With the need for electrical energy continuing to increase, various disturbances in the electrical system, including in substations, cannot be predicted when they will occur. The Power Breaker (PMT) is a vital equipment in the Bantul 150 kV substation power system that functions to break the electrical circuit under load to prevent interference and damage to equipment and ensure the smooth distribution of electrical energy to consumers. Based on the role of PMT, the estimation of PMT failure time has not been studied in depth. This study aims to analyze the Mean Time Between Failure and Reliability of the Bantul 150 kV Substation PMT. The method used in assessing PMT life is Maximum Likelihood Estimation. The data used are the results of observations of ten different PMTs in Bantul Substation. The results of the analysis show that the average value of the time period between failures (MTBF) varies between different PMTs. The highest MTBF value is PMT Wirobrajan 2 with a damage period of about 14.55 months, while the lowest MTBF is PMT Semanu 2 with a damage period of 5.48 months. The results of the analysis of failure probability, cumulative failure probability, reliability probability, and damage rate of 150 kV PMTs show significant variations between different PMTs. Reliability value produces the lowest value on PMT Transformer 3. While the highest Reliability value produces the highest value, namely on PMT Kopel. With the known MTBF and Reliability of 150 kV PMT at Bantul Substation, it can be used as a basis for maintenance and maintenance of PMT in its operation at Bantul Substation.